Is There Any Association between PEEP and Upper Extremity DVT?. (2nd April 2015) - Al-Saffar, Farah; Gupta, Ena; Siddiqi, Furqan; Faisal, Muhammad; Jones, Lisa M.; Seeram, Vandana; Louis, Mariam; Cury, James D.; Bajwa, Abubakr A.; Shujaat, Adil
Abstract : Background . We hypothesized that positive end-exploratory pressure (PEEP) may promote venous stasis in the upper extremities and predispose to upper extremity deep vein thrombosis (UEDVT). Methods . We performed a retrospective case control study of medical intensive care unit patients who required mechanical ventilation (MV) for >72 hours and underwent duplex ultrasound of their upper veins for suspected DVT between January 2011 and December 2013. Results . UEDVT was found in 32 (28.5%) of 112 patients. Nineteen (67.8%) had a central venous catheter on the same side. The mean ± SD duration of MV was13.2 ± 9.5 days. Average PEEP was7.13 ± 2.97  cm H2 O. Average PEEP was ≥10 cm H2 O in 23 (20.5%) patients. Congestive heart failure (CHF) significantly increased the odds of UEDVT (OR 4.53, 95% CI 1.13–18.11;P = 0.03 ) whereas longer duration of MV (≥13 vs. <13 days) significantly reduced it (OR 0.29, 95% CI 0.11–0.8;P = 0.02 ). Morbid obesity showed a trend towards significance (OR 3.82, 95% CI 0.95–15.4;P = 0.06 ). Neither PEEP nor any of the other analyzed predictors was associated with UEDVT. Conclusions . There is no association between PEEP and UEDVT. CHF may predispose to UEDVT whereas the risk of UEDVT declines with longer duration of MV.